A simple and green method for preparation of non-crystalline granular starch through controlled gelatinization. (15th February 2019) - Chen, Long; Tian, Yaoqi; McClements, David Julian; Huang, Meigui; Zhu, Bihua; Wang, Lingling; Sun, Binghua; Ma, Rongrong; Cai, Canxin; Jin, Zhengyu
Highlights: Non-crystalline granular starch (NCGS) was prepared by controlled gelatinization. The crystalline structure of native starch was thoroughly disappeared at 75 °C. Integral granular morphology of starch granules was maintained at 75 °C. B-type and V-type crystals formed in samples heated at 80 °C or higher. Abstract: Non-crystalline granular starch (NCGS) is of considerable interest because of its unique functional properties. In this study, controlled gelatinization combined with sedimentation was used to prepare the NCGS from normal maize starch. The morphology and crystalline state of the NCGS were investigated using optical and electron microscopy, calorimetry, and X-ray diffraction (XRD). These methods showed that starch granules maintained a granule structure up to around 80 °C but they completely dissociated at higher temperatures. The number of the granules that disappeared the birefringence gradually increased with the temperature increase, and completely disappeared at 75 °C. The DSC results indicated that the crystalline structure of amylopectin was totally destroyed when the treating temperature was greater than or equal to 75 °C. The XRD patterns showed that the crystalline structure of native starch was thoroughly disappeared at 75 °C. However, B-type and V-type crystals formed in the samples heated at 80 °C or higher, corresponding to the short-term retrogradation of amylose and the formation of amylose-lipids complexes, respectively.